Associação de água residuária da suinocultura e adubação mineral no cultivo de aveia-preta - Herrmann, Daniela da Rocha (2013)
Swine wastewater (SWW) has high organic load becoming an important source of macro and micronutrients to plants, promoting the improvement of soil quality and development in several tilth. however when done without agronomic and environmental standard, can cause problems in soil, leaching of nutrients, prejudice to water resources and toxicity to plants. The objective of this work, was to evaluate the chemical in soil and leachat regarding association of swine wastewater and mineral fertilization(MF) in farming black oat. Conducted an experiment using applications of SWW associated or not with MF, the treatments consisted of rates 0, 100, 200 and 300 m3ha-1 in the absence or presence MF, under field conditions. Were collected and analysis of soil and leachate in two seasons. It was observed effect associated with the wastewater and mineral fertilization on phosphorus in soil, isolated effect of mineral fertilization on the magnesium, potassium and electrical conductivity in soil and isolated effect of wastewater in the levels of pH, calcium, sodium, copper, zinc, nitrite + nitrate in soil and effect on sodium content in leachate